Bimbingan dan Konseling Keluarga: Pola Asuh Orang Tua dan Implikasinya terhadap Penanaman Nilai-Nilai Karakter pada Anak - Prio Utomo; Fiki Prayogi; Reza Pahlevi (UIN Siber Syekh Nurjati Cirebon, 2022)
One of the causes of a character crisis in children is due to inappropriate parenting factors, causing deviations in children's behavior. This study aims to represent parenting patterns and their influence on the formation of children's character values. This research was conducted in 2021, the research location in Kel. Bumi Ayu, Kec. Kec, Bengkulu City. The research method uses case studies. The results of the study obtained findings of parenting used by parents in instilling character values in their children using democratic parenting. The results of this study contribute as enrichment material both theoretically and practically regarding parenting patterns and their influence on instilling character values in children.